MEMBANGUN KESADARAN HUKUM MASYARAKAT MELALUI SOSIALISASI LEMBAGA BANTUAN HUKUM DI DESA SEMPAJAYA KABUPATEN KARO - Fajar Bahri; Andhara; Sabina Saeca Gultom; Sinvani Dinda Br Sitepu; Dina Miftahul Jannah; Larasati Ritonga; Isnaina Rizkia Ritonga; Tantri Rizky Alviani; Rasina Padeni Nasution (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2026)
This study addresses the issue of low legal awareness among rural communities in Indonesia, particularly in Desa Sempajaya, Karo Regency, where residents have limited knowledge of their legal rights and access to free legal aid. The research aims to enhance community understanding of the role and function of Legal Aid Institutions (Lembaga Bantuan Hukum/LBH) as guaranteed by Law No. 16 of 2011 on Legal Aid. Using a Participatory Action Research (PAR) approach, the program was implemented through preparation, socialization, and evaluation stages. Activities included collaboration with local government and legal aid posts, interactive presentations, discussions, and dissemination of procedures for obtaining legal assistance. The findings reveal that prior to the intervention, most residents lacked awareness of legal aid mechanisms and perceived legal processes as costly and complex. After the socialization, participants demonstrated improved knowledge of their legal rights, the existence of LBH, and the steps required to access free legal services. The program also highlighted challenges such as limited literacy, time constraints, and skepticism toward legal institutions. Overall, the socialization effectively strengthened community legal awareness and provided a foundation for developing a legally conscious village